What Powers the 2006 Outburst of the Symbiotic Star BF Cygni? - A. Skopal; M. Sekeráš; N. A. Tomov; M. T. Tomova; T. N. Tarasova; M. Wolf (Acta Polytechnica CTU Proceedings)
BF Cygni is a classical symbiotic binary. Its optical light curve occasionally shows outbursts of the Z And-type, whose nature is not well understood. During the 2006 August, BF Cyg underwent the recent outburst, and continues its active phase to the present. The aim of this contribution is to determine the fundamental parameters of the hot component in the binary during the active phase. For this purpose we used a high- and low-resolution optical spectroscopy and the multicolour UBV RCIC photometry. Our photometric monitoring revealed that a high level of the star’s brightness lasts for unusually long time of > 7 years. A sharp violet-shifted absorption component and broad emission wings in the Hα profile developed during the whole active phase. From 2009, our spectra revealed a bipolar ejection from the white dwarf (WD). Modelling the spectral energy distribution (SED) of the low-resolution spectra showed simultaneous presence of a warm (< 10 000 K) disk-like pseudophotosphere and a strong nebular component of radiation (emission measure of ~1061 cm−3). The luminosity of the hot active object was estimated to > 5−8×103 Lʘ. Such high luminosity, sustained for the time of years, can be understood as a result of an enhanced transient accretion rate throughout a large disk, leading also to formation of collimated ejection from the WD.